Understanding the rapid reduction of undernutrition in Nepal, 2001-2011 - Headey, Derek D.; Hoddinott, John F. (International Food Policy Research Institute, 2014)
Given recent interest in reducing undernutrition–particularly the role of nutrition-sensitive policies–this paper aims to quantitatively understand this surprising success story by analyzing the 2001, 2006, and 2011 rounds of Nepal’s Demographic Health Surveys. To do so, the authors first construct and test basic models of the intermediate determinants of child and maternal nutritional change and then decompose predicted changes in nutrition outcomes over time.